1995
DOI: 10.1111/j.1745-4603.1995.tb00785.x
|View full text |Cite
|
Sign up to set email alerts
|

FIBRE FRACTURE OF BOVINE M. PECTORALIS PROFUNDUS MUSCLE COOKED PRE‐ AND POSTRIGOR

Abstract: The ultimate tensile strength and extensibility in the direction of the muscle fibres of cooked meat decreased exponentially during storage of the raw meat for up to 3 days at 15C. The mode of fracture was examined by light microscopy of longitudinal sections taken after testing to break. In meat cooked soon after stunning, ‘brittle’ fracture had been induced across the fibres and the high extensibility was proposed to be due to sequential fibre fracture. At 1 day postmortem, the fractures crossed several fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The mechanical properties of meat are directly related to muscle structure, postmortem aging, and cooking (Bouton and Harris 1972;Davey and Gilbert 1977;Locker and Wild 1982;Purslow 1991). Tensile tests are widely used because they directly reflect muscle structures (Bouton and Harris 1972;Bouton et al 1975;Dansfield et al 1995;Mutungi et al 1995;Rao and Gault 1990;Sacks et al 1988). The tensile properties of meat can be used to monitor the changes in meat during the aging process (Locker et al 1983;Carroll et ul.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of meat are directly related to muscle structure, postmortem aging, and cooking (Bouton and Harris 1972;Davey and Gilbert 1977;Locker and Wild 1982;Purslow 1991). Tensile tests are widely used because they directly reflect muscle structures (Bouton and Harris 1972;Bouton et al 1975;Dansfield et al 1995;Mutungi et al 1995;Rao and Gault 1990;Sacks et al 1988). The tensile properties of meat can be used to monitor the changes in meat during the aging process (Locker et al 1983;Carroll et ul.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research has been conducted with regard to mechanical properties of meat and their relationship with tenderness measurement (Chrystall, 1994;Lepetit and Culioli, 1994;Tornberg, 1996). Tensile tests have been used to study mechanical properties of raw and cooked beef in relation to muscle structures and their changes caused by post-mortem treatments and cooking process (Bouton and Harris, 1972;Bouton et al, 1975;Carroll et al, 1978;Dansfield et al, 1995;Locker et al, 1983;Mutungi et al, 1995;Penfield et al, 1976;Rao and Gault, 1991;Sacks et al, 1988). Several studies have been reported on how tensile properties of cooked beef are related to tenderness measurement.…”
mentioning
confidence: 99%